2014
DOI: 10.1098/rstb.2013.0289
|View full text |Cite
|
Sign up to set email alerts
|

The mirror neuron system as revealed through neonatal imitation: presence from birth, predictive power and evidence of plasticity

Abstract: There is strong evidence that neonates imitate previously unseen behaviours. These behaviours are predominantly used in social interactions, demonstrating neonates' ability and motivation to engage with others. Research on neonatal imitation can provide a wealth of information about the early mirror neuron system (MNS), namely its functional characteristics, its plasticity from birth and its relation to skills later in development. Although numerous studies document the existence of neonatal imitation in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
162
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(177 citation statements)
references
References 110 publications
(204 reference statements)
9
162
3
3
Order By: Relevance
“…Simpson et al [16] suggested that this measure, the number of published experiments, gives a misleading impression because it does not take account of the sample size in each study. It is certainly not sufficient simply to count experimental outcomes, which is why Ray & Heyes [13] provided detailed methodological analysis of the whole corpus of imitation experiments involving newborns.…”
Section: Reason I: Newborns Can Imitatementioning
confidence: 99%
“…Simpson et al [16] suggested that this measure, the number of published experiments, gives a misleading impression because it does not take account of the sample size in each study. It is certainly not sufficient simply to count experimental outcomes, which is why Ray & Heyes [13] provided detailed methodological analysis of the whole corpus of imitation experiments involving newborns.…”
Section: Reason I: Newborns Can Imitatementioning
confidence: 99%
“…Early imitative abilities are associated with some aspects of later social cognitive development (37)(38)(39) and may reflect general social interest (for a review, see ref. 40). For example, macaque infants who consistently imitate in the first week of life, compared with those who do not, are better at recognizing human caregivers (38) and visually attend more to caregivers (39).…”
Section: Significancementioning
confidence: 99%
“…We gave ample space in this special issue to this topic [18][19][20][21][22]. It is highly debated whether the mirror system arose as the consequence of association learning or an evolutionary process that endowed a population of neurons with a mechanism necessary for accomplishing a specific function [20,23].…”
mentioning
confidence: 99%
“…The alternative account maintains that at least part of the mirror neuron system is genetically determined and adapted to serve one function as the consequence of the natural selection process ( [20], but also see [26,27]). More recently, models have been proposed which avoid pitting one view against the other, thus escaping an old fruitless nature-nurture divide.…”
mentioning
confidence: 99%